Forsvinder kønnets betydning i den excellente præstation? - Pedersen, Inge Kryger (Kvinder, Køn & Forskning, 1999)
This article discusses whether the achievement of excellence transcends gender. This thesis is evoked by research results that reveal that while a number of elite sports women reflect the problem of gender when establishing and maintaining a career in the sphere of elite sport, they do not consider questions about sex and gender in descriptions of their optimum achievements. The achievement of excellence is characterised by a sustained and precise form of success. Furthermore, it is a hyper cultural state , where nature is transformed and the bounds imposed by chromosomes overcome. The athlete becomes a symbol, the internal features of which transcend her facticity as a woman. She sees herself in a new and fascinatinf role by reason of her achievement and not by ascriptions as gender at the state of excellence only include the internal (or personal) features of the symbol? The new role in which the athlete sees herself must necessarily be related to the top achievement is a social event. The thesis is based on study results in the field of sport. However, the article aims to outline a thesis to be examined in gender studies within other spheres of society suck as the spheres of working life and art.